2014
DOI: 10.1080/09669582.2013.871018
|View full text |Cite
|
Sign up to set email alerts
|

Tourism's role in urban regeneration: examining the impact of environmental cues on emotion, satisfaction, loyalty, and support for Seoul's revitalized Cheonggyecheon stream district

Abstract: This study explores the use of sustainable tourism as a tool for the regeneration and "greening" of urban areas. It is based on evidence from the revitalization of the Cheonggyecheon stream district in downtown Seoul, a process that emphasized nature conservation and recreational opportunities. The purpose of this study is to examine the impact of environmental cues on emotion, satisfaction, loyalty, and support for the revitalized Cheonggyecheon stream district by applying a stimulus-organismresponse framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 84 publications
0
33
0
1
Order By: Relevance
“…High arousal also appeared to have powerful impact on inducing higher pleasure and satisfaction (Mattila & Wirtz, 2006). Many previous studies showed positive emotion as a significant antecedent of customer satisfaction in an attraction and a hotel (Lee, 2014;Lee, Lee, Choi, Yoon, & Hart, 2014;Lin & Worthley, 2012). In this study, four components of airport physical environments (i.e.…”
Section: Proposed Model and Research Hypothesesmentioning
confidence: 93%
“…High arousal also appeared to have powerful impact on inducing higher pleasure and satisfaction (Mattila & Wirtz, 2006). Many previous studies showed positive emotion as a significant antecedent of customer satisfaction in an attraction and a hotel (Lee, 2014;Lee, Lee, Choi, Yoon, & Hart, 2014;Lin & Worthley, 2012). In this study, four components of airport physical environments (i.e.…”
Section: Proposed Model and Research Hypothesesmentioning
confidence: 93%
“…Individuals are more likely to respond positively when their interactions with fellow travelers are positive (Grove and Fisk 1997), which can intensify their satisfaction and loyalty (Lee et al 2014). However, the behavior of others and the quality of customer-to-customer interactions can significantly detract from satisfaction and relaxation (Getz, O'Neill and Carlsen 2001), as it can exacerbate dissatisfaction with irksome activities such as queuing (Grove and Fisk 1997).…”
Section: Social Servicescapementioning
confidence: 99%
“…All items met the variance extracted estimate test, and thus, we treated all constructs separately. We used Harman's one‐factor test (Lee, Lee, Choi, Yoon, & Hart, ) to further establish discriminant validity. Harman's test compares the fit of the proposed multidimensional model against the fit of a one‐factor model.…”
Section: Resultsmentioning
confidence: 99%